Facile measurement of single-crystal elastic constants from polycrystalline samples - Xinpeng Du (Nature Portfolio, 2017)
Mechanical properties: a simpler method for determining elasticity A method for measuring the elastic properties of a material even with a less than perfect sample is demonstrated by scientists in the USA. Xinpeng Du and Ji-Cheng (J.C.) Zhao from The Ohio State University develop a simple experimental technique for obtaining elastic constants from polycrystalline samples. A material’s elasticity or stiffness properties are mathematically summarized by a series of parameters known as its elastic constants. Most experimental techniques for measuring these elastic constants require samples that are single-crystals. But these can be time consuming to produce or perhaps even impossible. Instead, Du and Zhao measure the velocity of so-called surface acoustic waves produced on a polycrystalline sample using pulses of laser light. They then develop a robust mathematical framework that can determine elastic constants based on material density and the measured velocities.